2014
DOI: 10.1007/s00774-014-0596-4
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of lycopene intake on bone loss in ovariectomized rats

Abstract: Antioxidant lycopene supplementation has been shown to decrease oxidative stress and have beneficial effects on bone health. However, it remains unclear whether lycopene exerts its beneficial effect on bone metabolism through mitigation of oxidative stress in vivo. The aim of this study was to investigate whether lycopene intake protects against bone loss by reducing oxidative stress in ovariectomized rats. Female Sprague-Dawley 6-week-old rats were ovariectomized and randomly divided into four groups accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
5
14
0
Order By: Relevance
“…A number of studies have demonstrated the beneficial effects of lycopene on bone metabolism [ 23 , 24 , 26 , 41 43 ]. In vitro studies have shown that lycopene promotes proliferation and differentiation of osteoblasts [ 26 , 44 ] and suppresses osteoclastogenesis and differentiation of osteoclasts in normal and OVX rats [ 26 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated the beneficial effects of lycopene on bone metabolism [ 23 , 24 , 26 , 41 43 ]. In vitro studies have shown that lycopene promotes proliferation and differentiation of osteoblasts [ 26 , 44 ] and suppresses osteoclastogenesis and differentiation of osteoclasts in normal and OVX rats [ 26 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The femoral bone strength at the middle diaphysis was examined by measuring the mechanical strength as previously reported 29 . Briefly, the force necessary to produce a break at the center of the femur was measured according to the following conditions: the sample space was 1.0 cm, the plunger speed was 100.0 mm/min, the load range was 50.0 kg, and the chart speed was 120.0 cm/min.…”
Section: Methodsmentioning
confidence: 99%
“…Lycopene has been shown in multiple studies to dose-dependently increase BMD in ovariectomized rats [ 151 ]. Similarly, lycopene reduced bone fragility in ovariectomized rats and improved femoral bone energy, as assessed using a mechanical breaking test [ 14 ]. More recently, lycopene supplementation in ovariectomized rats was found to significantly alter levels of biomarkers of bone turnover in blood and urine, reducing bone resorption and increasing osteoblast activity.…”
Section: Evidence Of the Effect Of Lycopene On Bone Healthmentioning
confidence: 99%
“… Schematic representation of the potential effects of lycopene on bone cells (reference from [ 13 , 14 , 99 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation